Femoral vascular conductance and peroneal muscle sympathetic nerve activity responses to acute epidural spinal cord stimulation in humans. Issue 6 (5th May 2018) - Holwerda, Seth W.; Holland, Marshall T.; Reddy, Chandan G.; Pierce, Gary L.
Abstract : New Findings: What is the central question of this research ? Does acute spinal cord stimulation increase vascular conductance and decrease muscle sympathetic nerve activity in the lower limbs of humans? What is the main finding and its importance ? Acute spinal cord stimulation led to a rapid rise in femoral vascular conductance, and peroneal muscle sympathetic nerve activity demonstrated a delayed reduction that was not associated with the initial increase in femoral vascular conductance. These findings suggest that neural mechanisms in addition to attenuated muscle sympathetic nerve activity might be involved in the initial increase in femoral vascular conductance during acute spinal cord stimulation. Abstract: Clinical cases have indicated an increase in peripheral blood flow after continuous epidural spinal cord stimulation (SCS) and that reduced muscle sympathetic nerve activity (MSNA) might be a potential mechanism. However, no studies in humans have directly examined the effects of acute SCS (<60 min) on vascular conductance and MSNA. In study 1, we tested the hypothesis that acute SCS (<60 min) of the thoracic spine would lead to increased common femoral vascular conductance, but not brachial vascular conductance, in 11 patients who previously underwent surgical SCS implantation for management of neuropathic pain. Throughout 60 min of SCS, common femoral artery conductance was elevated and significantly different from brachial artery conductance [in millilitres per minute: 15 min, change (Δ) 26 ± 37 versus Δ−2 ± 19%; 30 min, Δ28 ± 45 versus Δ0 ± 26%; 45 min, Δ48 ± 43 versus Δ2 ± 21%; 60 min, Δ36 ± 61 versus Δ1 ± 24%; and 15 min post‐SCS, Δ51 ± 64 versus Δ6 ± 33%; P  = 0.013]. A similar examination in a patient with cervical SCS revealed minimal changes in vascular conductance. In study 2, we examined whether acute SCS reduces peroneal MSNA in a subset of SCS patients ( n  = 5). The MSNA burst incidence in response to acute SCS gradually declined and was significantly reduced at 45 and 60 min of SCS (in bursts per 100 heart beats: 15 min, Δ−1 ± 12%; 30 min, Δ−14 ± 12%; 45 min, Δ−19 ± 16%; 60 min, Δ−24 ± 18%; and 15 min post‐SCS: Δ−11 ± 7%; P  = 0.015). These data demonstrate that acute SCS rapidly increases femoral vascular conductance and reduces peroneal MSNA. The gradual reduction in peroneal MSNA observed during acute SCS suggests that neural mechanisms in addition to attenuated MSNA might be involved in the acute increase in femoral vascular conductance. Abstract :